Numerical Evaluation of Different Adhesive Joint Configurations by Cohesive Zone Modelling - Barbosa, N. G. C.; Campilho, R. D. S. G. (Current Overview on Science and Technology Research Vol. 1, 2022)
The most common adhesive joint configurations are single-lap joints (SLJ), double-lap joints (DLJ), stepped joints and scarf joints. One of the most important parameters that affects the joint strength is the overlap length (LO). The main objectives of this work are to carry out a comparative study involving several joint geometries using various adhesives with different characteristics and to check which type of adhesive is most suitable for a particular joint geometry. For this purpose, SLJ, DLJ, stepped joints and scarf joints were chosen for testing with three adhesives. The numerical findings from the Abaqus® software's integrated cohesive zone modelling (CZM) module are compared to the experimental data. This research led to the conclusion that the type of adhesive being utilised has a substantial impact on the optimal joint arrangement.